The role of platelet rich plasma in knee joint pain - Thursina, Cempaka (Pakistan Medical Commission (PMC), 2022)
Osteoarthritis (OA) is a joint disorder is common worldwide. Pain and loss of function are the main clinical sign in knee joint OA that could come from periosteal nerve stretches, intraosseal hypertension, joint capsule stretches, intra-articular hypertension, ligament stretches, subchondral bone micro fracture, bursitis, and muscle spasm. Current therapy approach focuses on preventing progression and reducing symptoms by using a non-invasive procedure. Non-operative therapeutic intervention, that involves intra-articular injection in the knee joints, plays an important role in OA management. Platelet rich plasma (PRP) is a plasma fraction that contains concentrated platelets, has an autologue growth factor and high concentration of proteins that could improve healing process at cellular, tendon, ligament, muscle, as well as bone related tissue injury. Growth factor contained in PRP is responsible for anti-inflammatory effect through its inhibitory effect on Nuclear factor-kB (NFkB) cascade, thus it inhibits the inflammatory mediator production along with decreased COX2 expression. Roles of PRP towards NFkB deactivation could decrease chondrocyte inflammation, restore anabolic activity, and inhibit monocyte migration that could prevent OA progressivisity and reduce pain. PRP pathophysiology mechanism in healing process has made PRP an option for pain management in knee joint OA.